Introduction: evidence‐based action in humanitarian crises. (11th June 2013) - Dijkzeul, Dennis; Hilhorst, Dorothea; Walker, Peter
Abstract : This introductory paper sets the stage for this special issue of Disasters on evidence‐based action in humanitarian crises. It reviews definition(s) of evidence and it examines the different disciplinary and methodological approaches to collecting and analysing evidence. In humanitarian action, the need for evidence‐based approaches sometimes is viewed in tension with a principled approach, often unnecessarily. Choosing appropriate research methods depends on the objectives of the researcher, in particular whether the research focuses on the intervention and/or the context and the length and complexity of the causal chains involved. The paper concludes by defining some trends in evidence‐based approaches in crises: the move away from inputs and outputs of humanitarian action towards outcomes and impacts; the shift towards a higher degree of partnerships in research, and the participation of users and target groups; and the acceptance of a broad array of approaches to establish evidence.